Plant exploitation in Neolithic Sudan: A review in the light of new data from the cemeteries R12 and Ghaba. (15th August 2016) - Out, Welmoed A.; Ryan, Philippa; García-Granero, Juan José; Barastegui, Judit; Maritan, Lara; Madella, Marco; Usai, Donatella
Abstract: Little is known about the introduction of domesticated crops in Sudan. Substantial early evidence of the cereals wheat and barley has, until recently, been mainly restricted to the post-Neolithic, third millennium BC pre-Kerma site on Sai Island, and prehistoric finds in general are scarce. Interestingly, an analysis of phytoliths from plant depositions within burials and phytoliths and starch from dental calculus from the Nubian Middle Neolithic cemetery R12 and the Early Neolithic cemetery of Ghaba in Central Sudan has recently set back the date of domesticated cereal introduction in Sudan and Egypt by 500 years to around 7000 years ago. This paper presents new plant identifications from R12 and Ghaba that confirm the earlier data and give new information on the use of plants in burial contexts, including indications of processing of panicoid grasses at Ghaba. In addition, the paper presents an overview of the archaeobotanical data from Mesolithic and Neolithic Sudan and provides information about grass exploitation of mid-Holocene Egyptian sites that enables further interpretation of the R12 and Ghaba data. The grave goods from R12 and Ghaba, supported by comparable finds from other sites, show that the commonly attested mid-Holocene cemeteries offer a valuable archive that can substantially improve the understanding of the importance of both wild and domesticated plants in Sudan at the time of Neolithisation. In addition, the unexpected early presence of the domesticated cereals wheat and barley in Nubia, supported by finds from later periods, raises the hypothesis that cereal cultivation was practiced in this region from at least the Middle Neolithic onwards.